CHILDREN'S ENGLISH LANGUAGE ACQUISITION IN AN INDONESIAN FAMILY: PERSPECTIVES FROM LANGUAGE POLICY - Astutik, Astutik; Suryanto, Bradhiansyah Tri (Universitas Muhammadiyah Metro, 2024)
The primary purpose of this research is to find out the English language acquisition of children in Indonesian families. More specifically, this research analyzes the role of parents in children's acquisition of foreign language skills. The object of this research was taken from one of the families in the city of Probolinggo. The method used is Narrative Inquiry. Information was received through participant statements and interviews. It was analyzed using an inductive evaluation technique, including studying the transcript several times and identifying texts associated with the study's targets and observations. The results of this study reveal 3 points, namely parents' experiences, challenges faced by parents, and language policies.